Implementation of Cyber Notary as a Notary Transformation in the Digital Economy Era (Comparative Study of German Notary Law) - Handayani, Umi; Sulistiyono, Adi; Tejomurti, Kukuh (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The process of implementing the Cyber Notary concept in Indonesia still faces various obstacles due to the provisions in Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary or abbreviated as UUJN which still applies the principle of